If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8a + -2b)(8a + 2b) = 0 Multiply (8a + -2b) * (8a + 2b) (8a * (8a + 2b) + -2b * (8a + 2b)) = 0 ((8a * 8a + 2b * 8a) + -2b * (8a + 2b)) = 0 Reorder the terms: ((16ab + 64a2) + -2b * (8a + 2b)) = 0 ((16ab + 64a2) + -2b * (8a + 2b)) = 0 (16ab + 64a2 + (8a * -2b + 2b * -2b)) = 0 (16ab + 64a2 + (-16ab + -4b2)) = 0 Reorder the terms: (16ab + -16ab + 64a2 + -4b2) = 0 Combine like terms: 16ab + -16ab = 0 (0 + 64a2 + -4b2) = 0 (64a2 + -4b2) = 0 Solving 64a2 + -4b2 = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '4b2' to each side of the equation. 64a2 + -4b2 + 4b2 = 0 + 4b2 Combine like terms: -4b2 + 4b2 = 0 64a2 + 0 = 0 + 4b2 64a2 = 0 + 4b2 Remove the zero: 64a2 = 4b2 Divide each side by '64'. a2 = 0.0625b2 Simplifying a2 = 0.0625b2 Take the square root of each side: a = {-0.25b, 0.25b}
| 2z+20=28 | | 14*6= | | 14*5= | | 8818*4= | | 2x-5y=15 | | (3x+5)(3x-5)=0 | | 8+2+4= | | y^2-4y+3= | | 8+2= | | -8x-11=4x+13 | | 8a-10b=101.6 | | -10+4= | | (-7b+2b-3)(5b-2b+4)=0 | | 5x+1=3x+29 | | (6-3*3)-7= | | 2a+4b-2a-b= | | 0=6s^2-11s+4 | | (a+2a+5)(a-3a-7)=0 | | 0=6s^2+11x-4 | | 5(2T-2)=20 | | 15k^2-7k=4 | | -42+2x=22-6x | | (x-7x+4)(2x-3x-6)=0 | | (6x+4)+2x-16=180 | | (5x-2)(7-5x+2x)=0 | | 5+2d=29 | | 11j=6j-5 | | .17*1.2= | | 27=4x+7 | | (4s+5)(3s+8s-9)=0 | | 3c+4=11 | | 9x-5x^2=-2 |